Nine heteroleptic copper(I)/silver(I) complexes prepared from phosphine and diimine ligands: syntheses, structures and terahertz spectra. (1st January 2020) - Sun, Ling-Zhi; Kuang, Xiao-Nan; Lin, Sen; Zhao, Li; Yu, Xiao; Li, Zhong-Feng; Min-Liu,; Xin, Xiu-Lan; Yang, Yu-Ping; Jin, Qiong-Hua
Graphical abstract: Nine different copper(I)/silver (I) complexes were synthesized by changing anions and ligands. All these nine complexes exhibit intriguing 1D-3D structures which is due to intermolecular interactions. These complexes display interesting luminescence in the solid state at room temperature. In addition, THz spectroscopy was also studied in this research. Abstract: Direct reactions under ambient conditions among copper/silver salts, diimine ligands and diphosphine ligands were carried out at different rations, generating nine novel Cu(I)/Ag(I) complexes, [Cu(Dpq)(dppp)](ClO4 ) (1 ), [Cu(Dppz)(dppp)](ClO4 ) (2 ), [Cu(Dpq)(POP)](ClO4 ) (3 ), [Cu(Dppz)(POP)](ClO4 ) (4 ), [Cu(Dpq)(xantphos)](ClO4 )·0.843CH2 Cl2 (5 ), [Cu(Dppz)(xantphos)](ClO4 )·2CH2 Cl2 (6 ), [Ag(Dpq)(xantphos)](ClO4 ) (7 ), [Ag(Dpq)(xantphos)](CF3 SO3 ) (8 ), [Ag(Dpq)(POP)](CF3 SO3 ) (9 ). Dpq = pyrazino[2, 3-f][1, 10]phenanthroline